RETRACTED: History of formation of the hercynan structures of the northern Nuratau ridge on the regional background - Fidaev D.T.; Isomatov Yu.P.; Riskulov Kh.A. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001